Audit of Maternal Near Miss Cases in A Tertiary Care Hospital of Mardan - Maimoona Qadir, Nabila Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency and causes of maternal near miss events at a tertiary care hospital of Mardan. Methodology: This descriptive cross sectional study was conducted at Gynaecology department of Mardan Medical Complex from January 2018 to December 2019.Cases of maternal near miss events were collected from the records of women who met the WHO criteria for near miss. All the data was entered into structured proforma and analysis done. Results: Total near miss cases were 215 and totallive births were 9,228. The near miss rate was 23/1000 and maternal near miss to maternal mortality ratio was 3.7:1.Mean age was 26±3.2 years.Age group of 21-30 years was the high risk group with 112(52%) cases, followed by 31-40 years age group with 81(38%) cases. 89(41%) patients were multigravidas and 77(36%) were grand multi gravidas. Gestational age of more than 28 was seen in 146(68%) women and less than 28 weeks in 17(8%) whereas 52(24%) were postnatal.184(86%) were unbooked cases. Regarding the causes of near miss events, haemmorhage was seen in 96(45%), hypertension in 53(24.6%), Sepsis in 26(12%), cardiac disease in 10(4.6%), anaphylactic shock in 8(4%), anesthetic complications in 6(3%), epilepsy and hepatic encephalopathy in 4(2%) each and 8(4%) were due to indirect causes. Conclusion: Near miss cases have many similarities with maternal deaths and give us knowledge about the issues that need to be solved in order to reduce the grave situations where a maternal death can be prevented. Keywords: Near miss, Mortality, Morbidity, Haemmorhage, Hepatic Encephalopathy, Sepsis